Evaluation of Information Security Readiness Using the KAMI Index 5.0 and ISO/IEC 27001:2022 - Beri Novriyadi; Muhammad Jazman; Megawati Megawati; M. Afdal (STMIK Banjarbaru, 2025)
Information security evaluation is a crucial process for organizations to assess their level of readiness and to establish clear security management roles and responsibilities. Higher education institutions, such as Tuanku Tambusai University of Heroes, have significant responsibilities in safeguarding sensitive data. The institution maintains extensive records that include students' personal information, academic transcripts, financial data, and information relating to faculty and staff. Given that multiple organizational units access this information, ensuring data protection and compliance with privacy regulations is paramount. This research purposes to assess the readiness and maturity of information security at Tuanku Tambusai Heroes University using the KAMI Index version 5.0, using the ISO/IEC 27001:2022 standard. This assessment covers six information security domains and shows maturity levels ranging from I+ to II, which indicates that the institution is at an early stage of development, with only the fundamental framework established. In addition, the completeness of the ISO/IEC 27001 implementation was assessed as “Unqualified”, with a score of 379, corresponding to maturity levels I+ to II. These findings highlight the need for targeted improvements to meet the requirements for ISO/IEC 27001:2022 certification.Key word: Evaluation; ISO/IEC 27001:2022; Information Security; KAMI Index AbstrakMengevaluasi keamanan informasi sangat penting bagi organisasi karena membantu menilai tingkat kesiapan keamanan informasi dan menentukan peran dan tanggung jawab manajer keamanan. Institusi pendidikan tinggi, seperti Universitas Pahlawan Tuanku Tambusai, bertanggung jawab untuk menjaga informasi sensitif. Institusi ini menyimpan sejumlah besar data mahasiswa, termasuk rincian pribadi, catatan akademis, informasi keuangan, dan data mengenai dosen dan staf. Karena banyak unit mengakses data ini, sangat penting untuk memastikan perlindungan dan kepatuhannya terhadap peraturan privasi. Studi ini bertujuan untuk menilai kesiapan dan kematangan keamanan informasi di Universitas Pahlawan Tuanku Tambusai menggunakan Indeks KAMI versi 5.0 dan standar ISO/IEC 27001:2022. Evaluasi, yang mencakup enam area keamanan informasi, mengungkapkan tingkat kematangan mulai dari I+ hingga II, yang menandakan bahwa institusi tersebut berada pada tahap awal, dengan hanya kerangka dasar yang tersedia. Lebih jauh, kelengkapan implementasi ISO/IEC 27001 dinilai sebagai